2019
DOI: 10.1186/s12862-019-1509-x
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated evolution and diversifying selection drove the adaptation of cetacean bone microstructure

Abstract: BackgroundThe transition from land to sea by the ancestor of cetaceans approximately 50 million years ago was an incredible evolutionary event that led to a series of morphological, physiological, and behavioral adaptations. During this transition, bone microstructure evolved from the typical terrestrial form to the specialized structure found in modern cetaceans. While the bone microstructure of mammals has been documented before, investigations of its genetic basis lag behind. The increasing number of cetace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
2
2
0
Order By: Relevance
“…find very little evidence of phylogenetic signal in their dataset, with Pagel’s λ parameter taking values 0.02≤λ≤0.07 across the various datasets and trials. This is consistent with other studies of Cg that used comparable datasets to analyze convergent features across many clades [ 45 , 46 ]. As a result, one would expect little difference between these results and those obtained with ordinary LDA.…”
Section: Methodssupporting
confidence: 91%
“…find very little evidence of phylogenetic signal in their dataset, with Pagel’s λ parameter taking values 0.02≤λ≤0.07 across the various datasets and trials. This is consistent with other studies of Cg that used comparable datasets to analyze convergent features across many clades [ 45 , 46 ]. As a result, one would expect little difference between these results and those obtained with ordinary LDA.…”
Section: Methodssupporting
confidence: 91%
“…Although in principle the phylogenetic signal could have a strong effect, in practice, Fabbri et al find very little evidence of phylogenetic signal in their dataset, with Pagel's λ parameter taking values 0.02�λ�0.07 across the various datasets and trials. This is consistent with other studies of Cg that used comparable datasets to analyze convergent features across many clades [45,46]. As a result, one would expect little difference between these results and those obtained with ordinary LDA.…”
supporting
confidence: 91%
“…The evolutionary process of genes can be well understood by selection pressure analysis. When positive selection genes were detected on the ancestral branch of cetaceans, their genes involved in osteoclast function underwent accelerated evolution, thus demonstrating that bone remodeling played an important role in their adaptation to the water environment [ 32 ]. Zhang et al have analyzed the TLR genes of 102 amphibian species and found that purification selection played a major role in amphibian TLR evolution [ 33 ].…”
Section: Discussionmentioning
confidence: 99%